The role of adaptive artificial intelligence in the field of education in preparing students for modern technologies: The role of adaptive artificial intelligence in the field of education in preparing students for modern technologies - Raufov, Rufat; Safarov, Laziz (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation: This article explores the role of adaptive artificial intelligence (AI) in education, focusing on how it prepares students for the demands of modern technologies. It highlights the personalized learning experiences provided by adaptive AI, which tailors educational content to individual learning styles and speeds. The paper discusses AI's contribution to developing key skills like problem-solving and critical thinking, essential for navigating the tech-driven world. Additionally, it examines how AI fosters continuous learning and practical application of theoretical knowledge through simulations and virtual labs. The article also addresses how AI-enhanced education promotes collaboration and communication among students, skills crucial in the technology sector.